Foreword from Handling Editor – 9th Edition - Rahmawati, Salfia (ASEAN Journal of Community Engagement, 2021)
We are delighted to present the 9th edition of AJCE, published in July 2021. We have selected eight of the best articles for this edition, consisted of Research Articles.